2018
DOI: 10.1177/0268355518804360
|View full text |Cite
|
Sign up to set email alerts
|

Performance changes of venous valves following tissue treatment with novel in vitro system

Abstract: Objectives The purpose of this study is to test venous valve performance and identify differences between native tissue and replacement devices developed with traditional tissue treatment methods using a new in vitro model with synchronized hemodynamic parameters and high-speed valve image acquisition. Methods An in vitro model mimicking the venous circulation to test valve performance was developed using hydrostatic pressure driven flow. Fresh and glutaraldehyde-treated vein segments were placed in the setup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As previously mentioned, an increase in collagen crosslinking due to glutaraldehyde fixation has also been found to increase tissue stiffness that results in decreased venous valve performance in vitro . 17 Therefore, the ideal xenograft for a bioprosthetic venous valve requires optimizing stability while maintaining native valve mechanical properties. This makes shrink temperature an important consideration in xenograft development to evaluate the degree of crosslinking and thermal stability independent of the mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, an increase in collagen crosslinking due to glutaraldehyde fixation has also been found to increase tissue stiffness that results in decreased venous valve performance in vitro . 17 Therefore, the ideal xenograft for a bioprosthetic venous valve requires optimizing stability while maintaining native valve mechanical properties. This makes shrink temperature an important consideration in xenograft development to evaluate the degree of crosslinking and thermal stability independent of the mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…While current glutaraldehyde fixation techniques can be adjusted for long-term endurance with cardiac valves, for venous valves, this fixation technique has resulted in decreased valve performance in vitro. 17,18 Specifically, Easson et al 17 demonstrated a significant increase in the stiffness of glutaraldehyde treated venous valves that led to a decrease in the geometric orifice area during performance testing at physiological flow rates. This poses a significant problem in the venous system, where the environment consists of much lower pressure and flow compared to the arterial, that may accelerate the failure of bioprosthetic venous valves.…”
Section: Introductionmentioning
confidence: 99%
“…The captured valve behaviours (e.g. opening time and geometric orifice area) were able to reflect the property difference between various BJV tissues (such as fresh and glutaraldehyde-treated) ( Easson et al, 2019 ). Fatigue property is one of the key indicators of the durability of a BJVC, and the ISO 5840 (2021) standard prescribes guidelines on fatigue assessment of heart valves ( ISO, 2021 ).…”
Section: Future Prospectsmentioning
confidence: 99%